Supporting English Language Learners with Formative Assessment in Primary Schools - Pipková, Andrea (Univerzita Pardubice, 2018)
This bachelor thesis is concerned with supporting English language learners with formative assessment in primary schools. In the theoretical part, the terms evaluation and assessment are clarified and differentiated. Subsequently, summative evaluation and formative assessment is explained and also the term feedback as a base of formative assessment is stated. Then, the role of assessment in second language acquisition is defined. Thirdly, functions and strategies of formative assessment are mentioned and finally, attitudes, motivational factors and influence of assessment on young learners are characterized. The practical part probes whether teachers and learners in a primary school assess formatively or not. If yes, how they undertake the assessment and how learners perceive formative assessment during English language lessons. For the purpose of the research, fully structured interviews with two English language teachers were conducted and an observation sheet was designed in order to observe 10 English language lessons and eventually be able to answer 3 research questions.
Podpora studentů anglického jazyka pomocí formativního hodnocení na základních školách
Keywords: formativní hodnocení; anglický jazyk; strukturovaný rozhovor; observance; první stupeň základní školy; formative assessment; English language learners; primary schools; observation; interview